2013
DOI: 10.4317/jced.51047
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simultaneous nicotine and alcohol use in periodontitis progression in rats: a histomorphometric study.

Abstract: Objective: The aim of this study was to evaluate the effects of alcohol and nicotine, when used alone or simultaneously, on the alveolar bone loss area resulting from ligature-induced periodontitis in rats. Study design: Forty adult male rats received a cotton ligature in the first lower molar sulcular area, and the animals were randomly assigned to different treatments (n = 10, each group) including daily peritoneal injections of saline solution (group A), submitted to self-administration of alcohol 25% (gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…6,23 Impaired host response and high levels of inflammatory biomarkers have been shown to have a detrimental effect on periodontal Animal studies have demonstrated significantly higher alveolar bone loss after exposure to alcohol. [24][25][26][27] These studies showed increased expression of inflammatory markers in the periodontal tissues, including prostaglandin E2, 24 TNF-a, 28 and IL-1b, 25 as well as significant changes in the expression of bone biomarkers in alveolar bone, including tartrate-resistant acid phosphatase, receptor activator of nuclear factor-kB ligand, and osteoprotegerin. 26 It is noteworthy that other rodent studies have failed to show detrimental effects of alcohol consumption on periodontal tissues.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…6,23 Impaired host response and high levels of inflammatory biomarkers have been shown to have a detrimental effect on periodontal Animal studies have demonstrated significantly higher alveolar bone loss after exposure to alcohol. [24][25][26][27] These studies showed increased expression of inflammatory markers in the periodontal tissues, including prostaglandin E2, 24 TNF-a, 28 and IL-1b, 25 as well as significant changes in the expression of bone biomarkers in alveolar bone, including tartrate-resistant acid phosphatase, receptor activator of nuclear factor-kB ligand, and osteoprotegerin. 26 It is noteworthy that other rodent studies have failed to show detrimental effects of alcohol consumption on periodontal tissues.…”
Section: Discussionmentioning
confidence: 95%
“…Impaired host response and high levels of inflammatory biomarkers have been shown to have a detrimental effect on periodontal health; however, the specific biologic mechanisms and causal chain by which alcohol consumption may affect periodontal tissues have not been clarified yet. Animal studies have demonstrated significantly higher alveolar bone loss after exposure to alcohol 24‐27 . These studies showed increased expression of inflammatory markers in the periodontal tissues, including prostaglandin E2, 24 TNF‐α, 28 and IL‐1β, 25 as well as significant changes in the expression of bone biomarkers in alveolar bone, including tartrate‐resistant acid phosphatase, receptor activator of nuclear factor‐κB ligand, and osteoprotegerin 26 .…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies on humans have shown no relation between periodontal disease and alcohol consumption [6][7] . The use of rat models has been applied in the evaluation of periodontal pathogenesis 8 and regarding the influence of risk indicator/factors, such as estrogen deficiency [9][10] , alcohol consumption [11][12][13][14][15][16] , nicotine 17 and simultaneous nicotine and alcohol use 18 on disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…The ligature was knotted on the buccal side. Periodontitis progression time was 7 days before starting the various treatments …”
Section: Methodsmentioning
confidence: 99%